Measurements of nitric oxide on the heme iron and β-93 thiol of human hemoglobin during cycles of oxygenation and deoxygenation - Xu, Xiuli (National Academy of Sciences, 2003)
Nitric oxide has been proposed to be transported by hemoglobin as a third respiratory gas and to elicit vasodilation by an oxygen-linked (allosteric) mechanism. For hemoglobin to transport nitric oxide bioactivity it must capture nitric oxide as iron nitrosyl hemoglobin rather than destroy it by dioxygenation. Once bound to the heme iron, nitric oxide has been reported to migrate reversibly from the heme group of hemoglobin to the β-93 cysteinyl residue, in response to an oxygen saturation-dependent conformational change, to form an S-nitrosothiol. However, such a transfer requires redox chemistry with oxidation of the nitric oxide or β-93 cysteinyl residue. In this article, we examine the ability of nitric oxide to undergo this intramolecular transfer by cycling human hemoglobin between oxygenated and deoxygenated states. Under various conditions, we found no evidence for intramolecular transfer of nitric oxide from either cysteine to heme or heme to cysteine. In addition, we observed that contaminating nitrite can lead to formation of iron nitrosyl hemoglobin in deoxygenated hemoglobin preparations and a radical in oxygenated hemoglobin preparations. Using (15)N-labeled nitrite, we clearly demonstrate that nitrite chemistry could explain previously reported results that suggested apparent nitric oxide cycling from heme to thiol. Consistent with our results from these experiments conducted in vitro, we found no arterial/venous gradient of iron nitrosyl hemoglobin detectable by electron paramagnetic resonance spectroscopy. Our results do not support a role for allosterically controlled intramolecular transfer of nitric oxide in hemoglobin as a function of oxygen saturation.